Biofertilizer For Increasing Growth And Yield Of Melon (Cucumis Melo L.) - Alifyah, Nabila; Betty Saragih, Nur; Maulana, Bagus; Sihotang, Saipul (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2025)
This study aims to develop biofertilizer from Metharizium sp. to increase the production of melon plants (Cucumis melo L.). The excessive use of chemical fertilizers has damaged soil quality and the environment in Indonesia. Environmentally friendly biofertilizers can be a solution to improve soil fertility and increase crop yields. The research was conducted in Serdang Bedagai Regency from April to July 2024. The research method includes land preparation, planting, making granular compost, fertilizer application, and data analysis. The study is expected to provide an effective Metharizium sp. granular fertilizer formulation to increase melon production and reduce the use of chemical fertilizers.